Berberine nanoparticles with enhanced in vitro bioavailability: characterization and antimicrobial activity - Sahibzada MUK; Sadiq A; Faidah HS; Khurram M; Amin MU; Haseeb A; Kakar M (Dove Medical Press, 2018)
Muhammad Umar Khayam Sahibzada,1,2 Abdul Sadiq,2 Hani S Faidah,3 Muhammad Khurram,4 Muhammad Usman Amin,4 Abdul Haseeb,5,6 Maria Kakar4 1Department of Pharmacy, Sarhad University of Science and Information Technology, Peshawar, Pakistan; 2Department of Pharmacy, University of Malakand, Chakdara, Pakistan; 3Department of Microbiology, Faculty of Medicine, Umm Al Qura University, Makkah, Saudi Arabia; 4Department of Pharmacy, Abasyn University, Peshawar, Pakistan; 5Discipline of Social and Administrative Pharmacy, School of Pharmaceutical Science, Universiti Sains Malaysia, Peneng, Malaysia; 6Department of Clinical Pharmacy, College of Pharmacy, Umm Al Qura University, Makkah, Saudi Arabia Background: Berberine is an isoquinoline alkaloid widely used in Ayurveda and traditional Chinese medicine to treat illnesses such as hypertension and inflammatory conditions, and as an anticancer and hepato-protective agent. Berberine has low oral bioavailability due to poor aqueous solubility and insufficient dissolution rate, which can reduce the efficacy of drugs taken orally. In this study, evaporative precipitation of nanosuspension (EPN) and anti-solvent precipitation with a syringe pump (APSP) were used to address the problems of solubility, dissolution rate and bioavailability of berberine. Methods: Semi-crystalline nanoparticles (NPs) of 90–110 nm diameter for APSP and 65–75 nm diameter for EPN were prepared and then characterized using differential scanning calorimetry (DSC) and X-ray powder diffractometry (XRD). Thereafter, drug content solubility and dissolution studies were undertaken. Berberine and its NPs were evaluated for their antibacterial activity. Results: The results indicate that the NPs have significantly increased solubility and dissolution rate due to conversion of the crystalline structure to a semi-crystalline form. Conclusion: Berberine NPs produced by both APSP and EPN methods have shown promising activities against Gram-positive and Gram-negative bacteria, and yeasts, with NPs prepared through the EPN method showing superior results compared to those made with the APSP method and the unprocessed drug. Keywords: berberine, EPN, APSP, bioavailability, dissolution, antibacterial activity, precipitation method